2019
DOI: 10.1080/21691401.2019.1577883
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SBF2-AS1 promotes the progression of cervical cancer by regulating miR-361-5p/FOXM1 axis

Abstract: Long non-coding RNAs (lncRNAs) have been identified as critical players in tumorigenesis. Previous studies revealed that lncRNA SBF2-AS1 was involved in tumor progression. However, the role and underlying mechanism of SBF2-AS1 in cervical cancer (CC) remain unknown. In the present study, our data showed that SBF2-AS1 expression was significantly increased in CC. High SBF2-AS1 expression was associated with advanced FIGO stage and lymph node metastasis of CC patients. Function assays showed that SBF2-AS1 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 22 publications
5
60
0
Order By: Relevance
“…For example, lncRNA SOX21-AS1 accelerates CC development by sponging miR-7 and targeting VDAC1 [15]. LncRNA SBF2-AS1 contributes to the development of CC by modulating the miR-361-5p/FOXM1 axis [16]. LncRNA RP11-552M11.4 is conducive to oncogenesis and development of CC through regulating miR-3941/ATF1 signaling pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA SOX21-AS1 accelerates CC development by sponging miR-7 and targeting VDAC1 [15]. LncRNA SBF2-AS1 contributes to the development of CC by modulating the miR-361-5p/FOXM1 axis [16]. LncRNA RP11-552M11.4 is conducive to oncogenesis and development of CC through regulating miR-3941/ATF1 signaling pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the logarithmically growing cells (1 Â 10 4 /well) were inoculated into 96-well culture plates and cultured for indicated times. Then 10 lL CCK-8 solutions were added and incubated for 2 h at 37 C. Absorbance at 450 nm was measured using a microtiter plate reader (Bio-Rad, CA) [13].…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…SBF2-AS1 is a 2708 nt antisense RNA to SBF2, which is located at the 11p15.1 locus [11]. Recent studies showed that SBF2-AS1 might play critical roles in tumor progression, such as lung cancer, cervical cancer, esophageal squamous cell carcinoma, and liver cancer [12][13][14][15]. However, the roles and underlying mechanisms of SBF2-AS1 in AML remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lncRNA LOC105374902 promotes the malignancy of CC cells by acting as a sponge of miR-1285-3p, a process enhanced by TNF-α (25). Furthermore, the lncRNA SBF2-AS1 promotes the progression of CC by regulating the miR-361-5p/FOXM1 axis (26), while the lncRNA BDNF-Anti-Sense is downregulated in CC and possesses anti-tumor functions by negatively associating with brain-derived neurotrophic factor (27). RP11-480I12.5 is a newly identified lncRNA and, to the best of our knowledge, has not yet been extensively studied.…”
Section: Discussionmentioning
confidence: 99%